Integrasi Pasar Vertikal Gula Tebu (sugar cane) di Provinsi Lampung - Nia Rosiana (Universitas Teuku Umar, 2016)
Provinsi Lampung is the one of centers sugar cane smallholders with productivity levels reached 5.845 tons/ha. In addition, the level of production reached 67 047 tons and a total area of 11 471 ha crop yield (Disbun Lampung, 2014). The price of sugar cane which tends to fluctuate due to changes in supply-demand in domestic and world price of sugar cane. Fluctuations in the world price of sugar cane impact on sugar cane price change the consumer level in Lampung Province. However, such price changes are transmition up to the level of manufacturers. This article examines how quickly such price changes can be responded by each institution marketing through the analysis of the integration of vertical market results showed that the change in consumer prices at the earlier time was not transmitted properly to the hands of the manufacturer ( farmers) at this time. This resulted in farmers who did not accept the change in the price of sugar at consumer level. Farmers tend as recipients price (price taker) and is not affected by the reference market or local markets. Elasticity results show that most agencies respond quickly to changes in consumer prices that distributors and wholesalers.